2010
DOI: 10.1002/srin.201000017
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Lime in Synthetic ‘FeO’‐SiO2 and CaO‐‘FeO’‐SiO2 Slags

Abstract: Dissolution of different CaO samples into molten synthetic ‘FeO’‐SiO2 and ‘FeO’‐SiO2‐CaO slags was carried out in a closed tube furnace at 1873 K. The slag was kept stagnant. It was found that the dissolution rate was very fast when CaO rod was dipped into ‘FeO’‐SiO2 slag. In the case of ‘FeO’‐SiO2‐CaO slag, the dissolution of CaO rod in the stagnant slag was retarded after the initial period (2 minutes). Only less than 16 percent CaO reacted with the slag, irrespective of the type of lime. Three phase‐regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 17 publications
4
46
2
Order By: Relevance
“…The maintained heating rate was 400°C per hour. The desired temperature of the process was reached and held for 30 minutes, lime samples heated up to the same temperature in order to limit the thermal buoyancy, respectively, were added into the melt with the density of 2.9 g/cm 3 . Lime samples were prepared in the form of cylinders with height of 1.72-1.75 cm, diameter of 0.5 cm and density of 3.0 g/cm 3 using press machine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintained heating rate was 400°C per hour. The desired temperature of the process was reached and held for 30 minutes, lime samples heated up to the same temperature in order to limit the thermal buoyancy, respectively, were added into the melt with the density of 2.9 g/cm 3 . Lime samples were prepared in the form of cylinders with height of 1.72-1.75 cm, diameter of 0.5 cm and density of 3.0 g/cm 3 using press machine.…”
Section: Methodsmentioning
confidence: 99%
“…Elizaveta CHEREMISINA, 1) * Johannes SCHENK, 1) Ludwig NOCKE, 2) Alexander PAUL 3) and Gerald WIMMER 4) 1) Department of Metallurgy, Montanuniversität Leoben, 8700 Austria.…”
Section: Influence Of Magnesium Oxide Content On Kinetics Of Lime Dismentioning
confidence: 99%
“…ated from lime matrix. 4) Carbon dioxide and steam gas generated by the thermal decomposition of CaCO 3 , that is remained limestone after calcination, and Ca(OH) 2 which was formed by absorption of moisture in the air, can crush the 2CaO·SiO 2 layer on the surface of the lime. These thermal decomposition reactions are endothermic; thus, supply of heat from molten slag to lime is essential and thermal conductivity is necessary to postulate this thermal behavior.…”
Section: Thermal Conductivity Of 2cao·sio 2 Bearing Solid Solutionmentioning
confidence: 99%
“…Dissolution of lime into molten slag would proceed by two step reactions, namely, the formation of 2CaO·SiO 2 on the surface or in the vicinity of the lime and dissolution of 2CaO·SiO 2 into molten slag, where the rate-controlling step is regarded as mass transfer of 2CaO·SiO 2 in the slag phase. [1][2][3] To promote the dissolution of lime, elevation of temperature is a key factor because the solubility of 2CaO·SiO 2 would greatly depend on the temperature and increase with its elevation. For proper understanding of thermal condition regarding lime dissolution, thermal conductivity of 2CaO·SiO 2 is the most essential information.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many researchers [1][2][3] have reported that a 2CaO·SiO 2 layer is formed around lime during its dissolution into molten slag; this layer prevents further dissolution of lime. Noguchi et al 4) reported that the high content of FeO x in the CaO-SiO 2 -FeO x slag promotes…”
Section: Introductionmentioning
confidence: 99%